Electrochemical intramolecular cyclisation of propargyl bromoethers catalysed by nickel complexes - Duñach, E. (2005)
The electrochemical intramolecular cyclisation of propargyl 2-bromoethers 1-3 in N,N'-dimethylformamide at constant current in a diaphragmless cell has been developed using Ni(II) complexes as electron-transfer mediators. During controlled-current electrolyses of solutions of Ni(II) complexes in the presence of bromoethers, catalytic reduction of the latter proceeds via one-electron cleavage of the carbon–bromine bond to form a radical intermediate that undergoes cyclisation to afford the cyclic compounds in moderated to good yields.